Shoulder transcutaneous electric nerve stimulation decreases heart rate via potentiating vagal tone - Chun-Ming Hsieh (Nature Portfolio, 2021)
Abstract By enhancing vagal activity, auricle transcutaneous electric nerve stimulation (TENS) is developed as a non-invasive therapy for heart failure. Nevertheless, though shoulder TENS used for treating adhesive capsulitis could affect vagal tone, its potential impact on heart functions remains unclear. In this study, electrocardiogram (ECG) and heart rate (HR) of subjects in response to sham, right-sided, or left-sided shoulder TENS (TENS-S, TENS-R, and TENS-L, respectively; 5 min) were recorded and analyzed. During the stimulation period, TENS-R constantly and TENS-L transiently decreased the HR of subjects; both TENS-R and TENS-L increased powers of the low- and high-frequency spectra. While TENS-R exhibiting no effect, TENS-L increased the ratio of low/high-frequency power spectrum indicating TENS-R decreased the HR through potentiating cardiac vagal tone. Collectively, these results suggest TENS could be an early and non-invasive therapy for heart failure patients before considering implant devices or devices are not feasible; moreover, therapists/physicians need to carefully monitor the potential adverse events during treatment for patient safety. Trial registration: The study protocol was registered in ClinicalTrials.gov (NCT03982472; 11/06/2019).